2014
DOI: 10.1016/j.compbiomed.2014.04.014
|View full text |Cite
|
Sign up to set email alerts
|

A review on segmentation of positron emission tomography images

Abstract: Positron Emission Tomography (PET), a non-invasive functional imaging method at the molecular level, images the distribution of biologically targeted radiotracers with high sensitivity. PET imaging provides detailed quantitative information about many diseases and is often used to evaluate inflammation, infection, and cancer by detecting emitted photons from a radiotracer localized to abnormal cells. In order to differentiate abnormal tissue from surrounding areas in PET images, image segmentation methods play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
307
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 327 publications
(315 citation statements)
references
References 154 publications
(197 reference statements)
0
307
1
7
Order By: Relevance
“…For more information calculating the probabilities for this method, the reader is encouraged to read Zhu et al62 and Yushkevich et al61 A major disadvantage of thresholding method is that the intensity histogram does not provide spatial information about the ROIs. Also, there is no consensus on the selection of an optimum threshold level because of the large variability of pathologies, low resolution, inherent noise, and high uncertainties in fuzzy object boundaries 31. Moreover, defining tumor volumes based on SUV thresholds has been widely challenged 63, 64.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For more information calculating the probabilities for this method, the reader is encouraged to read Zhu et al62 and Yushkevich et al61 A major disadvantage of thresholding method is that the intensity histogram does not provide spatial information about the ROIs. Also, there is no consensus on the selection of an optimum threshold level because of the large variability of pathologies, low resolution, inherent noise, and high uncertainties in fuzzy object boundaries 31. Moreover, defining tumor volumes based on SUV thresholds has been widely challenged 63, 64.…”
Section: Discussionmentioning
confidence: 99%
“…An extensive review study by Foster et al31 identified five sophisticated procedures of PET tumor segmentation, namely manual segmentation, thresholding‐based methods, learning methods and stochastic modeling‐based techniques, region‐based (graphical‐based) segmentation methods, and boundary‐based methods. The study concluded that there is no notion of one acceptable PET image segmentation method over the other.…”
Section: Introductionmentioning
confidence: 99%
“…10,19 All these methods offer different compromises in terms of versatility and performance and compare well against manual segmentations by clinicians or the pathological measurements with varying rates of success. 3 Yet there is not enough consensus among the clinical community on algorithms that work well to be incorporated into commercially available imaging software and treatment planning systems. 3,4 Most of these state-of-the-art algorithms are proprietary and are currently unavailable for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…The methods range from simple to complex methods. 1,3,4 The segmentation methods include but are not limited to constant and adaptive threshold methods, [5][6][7][8][9] region growing methods, [10][11][12] gradient-based methods, [13][14][15] fuzzy models, [16][17][18] and Gaussian mixture modeling. 10,19 All these methods offer different compromises in terms of versatility and performance and compare well against manual segmentations by clinicians or the pathological measurements with varying rates of success.…”
Section: Introductionmentioning
confidence: 99%
“…A review conducted by Foster et al on the state-of-the-art image segmentation methods for PET scans of body images, as well as the recent advances in PET image segmentation techniques, pointed resolution related issues, noise and large variability in the shape, texture, and location of pathologies as factors that significantly affect PET image segmentation. They also indicate to the lack of standardization between different segmentation techniques and the need for a publicly available database of PET images for evaluating new and old methods [13].…”
Section: Introductionmentioning
confidence: 99%